Perbaikan Sifat Aspal Penetrasi 60-70 Menggunakan Bahan Tambah Polimer Polypropylene (PP) - Gilang Nugraha; Rina Budiarti; Siegfried Syafier (Jurnal Teknik Sipil dan Teknologi Konstruksi, 2025)
Asphalt modification using polymer-based additives is one approach to improving resistance against plastic deformation and high temperatures. This study evaluates the effect of adding pure polypropylene (PP) on the physical and thermal properties of penetration grade 60/70 asphalt. PP was added at 0%, 1%, 3%, and 5% by weight. A reflux method was used to soften the polypropylene prior to mixing. Tests included penetration, softening point, viscosity, ductility, flash point, solubility, specific gravity, and TFOT. Results show reduced penetration from 61.8 to 49.7, increased softening point from 49.5°C to 53.2°C, and increased viscosity from 424 cSt to 592 cSt. Ductility decreased significantly from >140 cm to 122 cm, indicating reduced flexibility. The 5% PP addition gave the best stiffness and thermal stability. Storage stability tests were not conducted due to equipment limitations, suggesting the need for further study.